Housing and urban renewal in historic centers: A case study on Cuenca (Ecuador) - Pauta Calle, Fernando Victor (Estoa. Journal of the Faculty of Architecture and Urbanism, 2019)
This article addresses the housing problem in historical centers subjected to processes of urban renewal, from the perspective of the operation of land rent and impacts its conservation, as well as in the growth of cities, demonstrated in the case of Cuenca- Ecuador. Thus the study focuses on two processes of urban renovation of the historical center of Cuenca occurred between 1960 and 1995, covered by an urban crisis that was experienced in the first half of the eighties, and that signified considerable transformations of its functions, including the residential function, and the built heritage that hosted them. The conclusions show that the renewal processes under the interest of capital are harmful to historical spaces, because they enhance the valuation of private property of the land and together subject their rationality to housing and built heritage.